Alterations in levels of 8-Oxo-2'-deoxyguanosine and 8-Oxoguanine DNA glycosylase 1 during a current episode and after remission in unipolar and bipolar depression. (April 2020) - Ceylan, Deniz; Yılmaz, Selda; Tuna, Gamze; Kant, Melis; Er, Ayşe; Ildız, Ayşegül; Verim, Burcu; Akış, Merve; Akan, Pınar; İşlekel, Hüray and Veldic, Marin and Frye, Mark and Özerdem, Ayşegül
Highlights: Patients with depression have higher urine levels of 8-oxo-dG, lower expression levels of OGG1 than healthy controls. Patients with unipolar and bipolar depression did not differ with respect to urine 8-oxo-dG and OGG1 expression levels. Patients presented decreased urine levels of 8-oxo-dG, increased expression levels of OGG1 by remission of depression. Abstract: Introduction: Previous studies showed significant increases in DNA base damage markers and significant alterations in base excision repair enzymes in patients with unipolar and bipolar depression. We aimed to investigate changes in urine 8-Oxo-2′-deoxyguanosine (8-oxo-dG) and gene expression levels of 8-Oxoguanine DNA glycosylase 1 ( OGG1 ) during a current depressive episode and after remission in bipolar and unipolar disorders. Methods: Twenty-four acutely depressed bipolar (BD), 33 unipolar depression (UD) patients and 61 healthy controls were included in the study. Clinical evaluations, blood and urine sampling were completed at baseline and at remission after eight weeks. The urine 8-oxo-dG levels were assessed by liquid chromatography tandem mass spectrometry and adjusted for urine creatinine levels. The gene expression levels of OGG1 were determined from cDNA extracted from blood samples, using real time-polymerase chain reaction. Results: At baseline, patients presented significantly higher levels of 8-oxo-dG (p = 0.008), and lower gene expression of OGG1 (p = 0.024) compared to controls. Levels of either 8-oxo-dG or OGG1 expression did not differ between BD and UD. In patients who remitted by the 8th week (n = 30), 8-oxo-dG decreased significantly (p = 0.001), and gene expression levels of OGG1 increased by 2.95 times compared to baseline levels (p = 0.001). All comparisons were adjusted for age, sex, smoking status and body mass index. Conclusion: Our results suggest that patients with bipolar and unipolar mood disorders present increased 8-oxo-dG and decreased gene expression levels of OGG1 in current depressive episodes, and that these changes might be reversed by the resolution of depressive symptoms. The causal relationship between DNA damage and repair requires further exploration.